About the international seminar «Hydrogen power as an alternative energy source» - V. D. Yulovskaja (Тонкие химические технологии, 2010)
Results of the International scientific and technical Seminar with elements of school for young scientists «Hydrogen power as an alternative energy source», spent on October, 20 - 23rd, 2009 in МITHT are considered. High scientific level of the presented reports is noted, are summed up III competition of young scientists.